Distribution of Botryosphaeria species causing grapevine dieback and decline in New Zealand vineyards - Baskarathevan, J.; Jaspers, M.V.; Jones, E.E.; Ridgway, H.J. (New Zealand Plant Protection, 2008)
Worldwide 11 species of Botryosphaeria have been isolated from grapevines in association with a wide range of decline and dieback symptoms Currently there is little knowledge on what species are present in New Zealand A comprehensive survey was carried out during June to December 2007 to collect Botryosphaeria species from New Zealand vineyards More than 450 isolates including B parva B lutea B australis B stevensii B obtusa and B iberica were isolated from symptomatic material No correlation was observed between the species of Botryosphaeria and grapevine variety or age The highest incidence of Botryosphaeria species (977 ) was from Blenheim and lowest (164 ) was from Otago The most commonly isolated species was B parva followed by B stevensii Fusicoccum type Botryosphaeria species such as B parva and B lutea were more prevalent in the North Island and Diplodia type species including B stevensii and B obtusa dominated in the South Island It is likely that the Botryosphaeria species distribution in New Zealand is influenced by climatic conditions This information has implications for development of control strategies